Implementation Of The Undergraduate Scholarship Program For Society in Sidoarjo District - Setiyani, Nur Fitria; Arif, Lukman (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The number of people aged 15 and over who have completed undergraduate program in Sidoarjo district remains modest when compared with several other cities or districts in East Java, with a percentage of 18.34%. The government of Sidoarjo has established a undergraduate scholarship program for local collage students, to ensure that individuals have the opportunity to complete their studies without financial constraints. This scholarship program is designed to support collage students in their academic and non-academic achievements, recognizing and honoring their efforts and accomplishments. The purpose of this research is to describe and analyze the implementation of the undergraduate scholarship program in Sidoarjo district. This research utilizes a qualitative descriptive research method, incorporating techniques such as observation, interviews, and documentation to collect data. This research employs David C. Korten’s theory (1988) of program implementation, which has three components: the program, the structure of the implementing organization, and the beneficiaries of the program. The findings of this study indicate a degree of suitability among the program, the implementing organization, and the beneficiaries, suggesting a positive correlation with the implementation process. Nevertheless, a discrepancy exists between the prevailing regulations and the stipulated requirements, as evidenced by the discrepancy between the regulations' theoretical application and their practical implementation. The aforementioned discord has engendered a sense of inequity in the allocation of the undergraduate scholarship program.